Prioritizing the implementation of e-learning tools to enhance the learning environment - Percival, Jennifer Catherine; Muirhead, Bill (International Journal of E-Learning & Distance Education / Revue internationale du e-learning et la formation à distance, 2009)
The implementation of both blended learning and web-based programs is becoming more prevalent within higher education in Canada. Thus, there is increasing reliance upon e-learning tools to support student learning in a variety of teaching environments. Typically, budgetary and programmatic decisions regarding the investment of e-learning resources are made by information technology (IT) administrators and/or professors. However, students are the primary beneficiary of most IT investments. This study examined Business and IT students’ usage patterns and perceptions related to a suite of e-learning tools through open ended and Likert scale survey questions. Findings will assist post-secondary decision-makers in prioritizing IT investments. Further, study results will ensure that the design and implementation of e-learning tools address the needs and usage patterns of the primary client—the student. Résumé L’implantation des programmes d’apprentissage hybride et basés sur le Web devient de plus en plus courante dans les études supérieures au Canada. Donc, il y a une plus grande utilisation des outils eLearning pour soutenir l’apprentissage étudiant dans une variété d’environnements d’enseignement. Typiquement, les décisions touchant les budgets et les programmes concernant l’investissement de ressources en eLearning sont prises par les administrateurs des services de technologie de l’information (IT) et/ou des professeurs. Cependant, les étudiantes et les étudiants sont les premiers bénéficiaires de la plupart des investissements en IT. Cette étude examine les profils d’utilisation d’étudiants en commerce et en technologie de l’information des outils eLearning mis à leur disposition, grâce à des questions ouvertes et à un sondage utilisant une échelle de Likert. De plus, les résultats de l’étude permettront de s’assurer que le design et l’implantation d’outils eLearning répondent aux besoins et au profil d’usager du premier concerné, l’étudiant.